(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This Qualitative Study, Adopting A Phenomenological Approach, Investigates the Experiences and Perceptions of Undergraduate Digital Media Students at the University of Jeddah Regarding An E-Learning Environment Based on Generative Artificial Intelligence (GenAI) During Their Study of the “Digital Culture” Course, and Explores Its Roles in Developing the Cognitive and Performance Dimensions of Their Digital Learning Capabilities. Data Were Collected Through (12) Semi-Structured Individual Interviews and Analyzed in Depth Following a Thematic Analysis Approach. The Findings Revealed Three Main Categories: (1) Innovative Learning Experience Which Included Sub-Themes Such As Students’ Perceptions Of The Model and Active Engagement With Its Components; (2) Dimensions of Digital Learning Capabilities, Which Showed Notable improved Across Six Sub-Dimensions: Digital Productivity, Information Literacy, Creative Digital Production And Problem-Solving, Digital Interaction And Collaboration, Self-Directed Learning, and Responsible Digital Practices Including Identity and Well-Being; (3) Students’ Perspectives on Sustaining the Use of This Environment, Which Encompassed Sustainability Requirements and Technical Challenges. The Study Demonstrated Generative AI-Supported Learning Environments and Represent a Promising Educational Tool for Reshaping University Teaching and Learning Practices, If Implemented Within a Well-Informed Pedagogical Vision and Guided by Clear Regulatory and Ethical Frameworks. Research Recommends Integrating Generative AI Models into University Curricula, In Addition to Providing Specialized Training Programs, and Enhancing the Technological Infrastructure to Ensure Their Sustained Educational Impact.